Analysis of the Relationship between Scrubber Performance and Engine Operational Performance on MV. Sinar Sorong - Anang Satriaji; Ali Azhar; Kuncowati; Supartono (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The implementation of exhaust gas cleaning systems (scrubbers) has become a critical compliance strategy for maritime vessels following the International Maritime Organization's 2020 Global Sulphur Limit regulation. However, the technical relationship between scrubber performance and main engine operational reliability remains insufficiently documented in empirical maritime research. This study aims to analyze the correlation between scrubber performance and engine operational performance on the container vessel MV. Sinar Sorong through a quantitative approach utilizing technical parameter measurements and structured questionnaires. Data were collected during operational periods from April to December 2025, encompassing chemical performance parameters of coagulant and flocculant agents, engine performance metrics including maximum combustion pressure, compression pressure, exhaust gas temperature, and specific fuel oil consumption. The research employed 29 respondents from the engine department selected through purposive sampling technique, with data analyzed using Pearson correlation and linear regression in SPSS version 26. Results demonstrate a positive and statistically significant correlation (r = 0.587, p = 0.001) between scrubber performance and engine operational performance, with regression analysis indicating that 96.9% of engine performance variance can be explained by scrubber efficiency. The scrubber system maintained optimal technical parameters with nonvolatile solid content of 34.1%, viscosity of 420 cPs, basicity level of 40%, and pH range of 3.5-8.2, effectively reducing sulfur oxide emissions while maintaining engine stability. Main engine parameters remained within optimal design specifications: maximum combustion pressure 145.4 bar, compression pressure 107.2 bar, exhaust gas temperature 333°C, and specific fuel consumption 174.0 g/kWh. This research contributes empirical evidence that scrubber systems function beyond regulatory compliance instruments, serving as technical components that enhance combustion system stability through sulfur residue reduction and corrosive deposit prevention in exhaust pathways. The findings provide practical implications for maritime operators to implement integrated preventive maintenance strategies and real-time monitoring systems to sustain the synergistic relationship between scrubber efficiency and engine reliability, ultimately optimizing operational efficiency and extending critical component lifespan.